Synthesis of spirocyclic tetrahydroisoquinolines (spiroTHIQs) via the Castagnoli-Cushman reaction. Issue 42 (15th October 2020) - Safrygin, Alexander; Dar'in, Dmitry; Bakulina, Olga; Krasavin, Mikhail
Graphical abstract: Three component Castagnoli-Cushman reaction of homophthalic anhydride, cyclic ketones and ammonium acetate followed by decarboxylation and lactam reduction provided the shortest reported route to spirocyclic tetrahydroisoquinolines (spiroTHIQs). Highlights: Tetrahydroisoquinolines (THIQs) are privileged motifs for drug design. THIQs containing a spiro center at position 3 are scarce. Such scaffolds have been accessed via a three-step approach. Step 1: the recently developed variant of the Castagnoli-Cushman reaction. Steps 2–3: decarboxylation followed by lactam reduction. Abstract: A new route to privileged spirocyclic tetrahydroisoquinolines (spiroTHIQs) has been developed. The key step in which the spirocyclic system is formed in generally good yields and diastereoselectivity is the three-component Castagnoli-Cushman reaction of homophthalic anhydride, cyclic ketones and ammonium acetate. Decarboxylation of the initial adduct yields THIQ lactams which are reduced by lithium aluminum hydride. The route is shorter, more convergent and operationally simpler than the previously reported syntheses of similar spirocyclic building blocks.